Public Policy Innovation in Indonesia: Enchancing Citizen Engagement through E-Government Initiatives - Susniwati, Susniwati; Kurniawati, Kurniawati; Susilawati, Susilawati (Universitas Negeri Makassar, 2024)
Public policy innovation has become a critical focus in Indonesia's efforts to enhance citizen engagement and improve governance. With the rise of digital technology, the government has increasingly adopted e-government initiatives to streamline services and increase transparency. This study examines the effectiveness of e-government platforms in fostering greater citizen participation in public policy processes. The research aims to identify how digital innovations can bridge the gap between government and the public, improving accessibility and accountability in policy-making. Using a mixed-method approach, both qualitative and quantitative data were collected from various government agencies, citizens, and policy experts. Surveys and interviews were conducted to assess the perception of e-government services, while secondary data analysis evaluated the adoption and impact of these initiatives across different regions in Indonesia. The findings reveal that while e-government platforms have succeeded in simplifying administrative processes, challenges remain in ensuring equitable access for all citizens, particularly in rural areas. Furthermore, the study highlights the need for continuous improvement in digital literacy and infrastructure to fully leverage the potential of e-government. The research concludes that a more inclusive approach to public policy innovation, supported by comprehensive e-government strategies, can significantly enhance citizen engagement and contribute to more transparent and participatory governance in Indonesia.